DIXDC1 increases the invasion and migration ability of non‐small‐cell lung cancer cells via the PI3K‐AKT/AP‐1 pathway. Issue 11 (29th June 2013) - Xu, Zhonghai; Liu, Di; Fan, Chuifeng; Luan, Lan; Zhang, Xiupeng; Wang, Enhua
Abstract DIX domain containing 1 (DIXDC1), is a human homolog of Ccd1, a recently identified DIX domain containing protein in zebrafish. DIXDC1 protein was detected in human colorectal adenocarcinoma tissues and was found to be correlated with a high cell proliferation index. We demonstrated DIXDC1 overexpression in 55% (92/167) of non‐small cell lung cancer (NSCLC) cases, compared to adjacent noncancerous lung tissues (P < 0.01). Overexpression of DIXDC1 was associated with lymph node metastasis and more advanced TNM stage (P < 0.001 and P = 0.001, respectively). Kaplan–Meier survival curves and log‐rank testing indicated that overexpression of DIXDC1 correlated with worse overall survival in NSCLC (P = 0.031). DIXDC1 was more abundant in seven NSCLC lines than the bronchial cell line HBE, and modulation of its expression regulated AP‐1 activity; MMP2, MMP7, and MMP9 protein and mRNA; and invasion ability. Metalloproteinase induction was reversed by PI3K/AKT and AP‐1 inhibition. These results suggest DIXDC1 is associated with stage and prognosis in NSCLC, and may promote invasion and migration through PI3K‐AKT/AP‐1‐dependent activation of metalloproteinases. © 2013 Wiley Periodicals, Inc. © 2013 Wiley Periodicals, Inc.